IMPROVEMENT OF COMMUNICATION SKILLS AND MATHEMATICAL DISPOSITION OF STUDENTS GIVEN A MODEL PROBLEM BASED LEARNING AND DISCOVERY - Rosmita Sari Siregar (Nusantara Hasana Journal, 2022)
Communication skills and dispositions is very important mathematical owned by students to solve problems concerning mathematical concepts. In this study, analyzed the differences increase communication skills and dispositions given mathematical model of problem based learning and discovery. The method used in this research isquasi experiment and sampling techniques performed with simple random sampling.Inferential analysis of data performed by analysis of covariance, The results showed that increased communication abilities were given a mathematical problem based learning models larger than the discovery at 12.61. This is evident from the difference in value of the constant regression model of problem based learning is 31.89 and discovery that is 19.28, and increased by mathematical disposition of problem based learning models larger than the discovery of 12.41, This is evident from the difference score regression equation constant problem based learning models that 42.69 is greater than the discovery that 30.28,